Masa Kerja, Sikap Kerja Dan Jenis Kelamin Dengan Keluhan Nyeri Low Back Pain - AZ, Rasyidah; Dayani, Hazria; Maulani, Maulani (Universitas Fort De Kock Bukittinggi, 2019)
Low Back Pain (LBP) is one of the health problems that are often found in the community. Every year 15-45% of adults suffer from low back pain, and one in 20 sufferers must be hospitalized due to acute attacks. Risk factors that influence the occurrence of low back pain include work period, work attitude and gender. This study aims to determine the relationship between Work Period, Work Attitude and Gender with Low Back Pain Pain Complaints in the Neurological Polyclinic of Royal Prima Jambi Hospital. The population in this study were all low back pain sufferers at the Nerve Polyclinic at Royal Prima Jambi Hospital from 425 people in May and sampling was done using accidental sampling technique which amounted to 78 patients. The analysis in this study using the Chi-square test. The results of the analysis show that there is a relationship between Work Period, Work Attitude and Gender with Low Back Pain Complaints in the Neurological Polyclinic of Royal Prima Jambi Hospital with a P-Value value of <0.05. There is a relationship between Work Period, Work Attitude and Gender with Low Back Pain Complaints in the Nerve Polyclinic Royal Prima Jambi Hospital. Keywords: Working Period, Work Attitude, Gender, Low Back Pain